Analytical method for compiling and applying a ballast map for the traction unit PE2U - Bannikov, Dmytro; Radkevich, Anatoliy (Eastern-European Journal of Enterprise Technologies, 2019)
Under practical operation, electric locomotive traction units of series PE2U quite often require, especially in recent decades, various kinds of repair, necessitating the restoration of fleet of these machines that are rather worn-out. That changes the most important indicator in the work of the machine ‒ the distribution of masses; the resulting imbalance of the machine can reach 30 %. Further operation of such a locomotive leads to a decrease in its traction by 40‒100 kN, shortens the service life of the undercarriage by 8‒10 years on average, as well as requires that the speed of the machine during operation should be reduced by 10‒15 km/h. Given the lack of an appropriate regulatory framework and of recommendations in the specialized literature, such balancing operations are actually performed iteratively, with an arbitrary arrangement of ballast elements, which often delays the duration of operations and leads to their poor quality. One of the possible solutions to resolve this issue is the development and implementation of a special theoretical method that would make it possible to analytically substantiate the proposed structural-technological solutions related to the arrangement of a ballast at the electric locomotive traction unit PE2U. In this case, the ballast is composed of individual small-size elements that are stacked in rows into existing structural cavities in a bearing frame. The result is a compiled so-called individual ballast map for each machine. The proposed approach includes two stages of calculations and makes it possible to not only obtain practically acceptable ballast location diagrams, but to also significantly reduce the number of weighings required for the machine. The approach has been tested on several machines at electric locomotive traction units of PE2U over 2010‒2012 and could be officially used in the specialized regulatory documentation. Its practical error does not exceed 3 % and is mainly predetermined by technological factors